Equitable, inclusive and sustainable public transit mobility through mobility on demand? A critical perspective - Ward, Chandra; Oakley, Deirdre (Frontiers in Sustainable Cities, 2022)
In recent decades, public transit authorities have increasingly opted to invest in commuter transit that caters to a whiter, wealthier demographic as opposed to lower-income transit-dependent populations. In addition, urban-suburban population shifts caused by central-city gentrification has meant that those who depend on public transit the most have been forced to move outside the city center. This presents challenges for transit-dependent riders, particularly in sprawling, car-dependent Southern US cities where transit agencies are spatially constrained and underfunded. Quite simply, the transit does not reach the destinations where the people who need it most are moving. Mobility-on-demand (MOD) has emerged in recent years as an innovative approach to sustainability through mobility. Increasingly, scholars are exploring its ability to increase access to opportunity areas (i.e.., shopping, employment, social commitments) previously disconnected because of transit spatial mismatching. In this paper, we situate the discussion of MODs within the larger context of the unequal development in cities. We discuss extant research on MODs, and an initiative being piloted in a medium-sized Southern US city, Chattanooga, Tennessee. Using a transit equity lens we explore, within the context of historical and present uneven development, whether MODs are truly disruptive in reducing transit disadvantage, can address the limits of the “city-centric” nature of fixed and sparse public transit in areas of the country with a poor history of public transit investment (e.g., the US South), and respond to the dynamic nature of regional migration that constitute cities in the 21st century.